Hematoma and abscess formation caused by Mycoplasma hominis following cesarean section - Hisato Koshiba, Akemi Koshiba; Yasushi Daimon; et al (Dove Medical Press, 2011)
Hisato Koshiba1,2, Akemi Koshiba1,2, Yasushi Daimon3, Toshifumi Noguchi1,2, Kazuhiro Iwasaku2, Jo Kitawaki21Department of Obstetrics and Gynecology, Kyoto Prefectural Yosanoumi Hospital, Kyoto, Japan; 2Department of Obstetrics and Gynecology, Kyoto Prefectural University of Medicine, Graduate School of Medical Science, Kyoto, Japan; 3Department of Clinical Laboratory, Kyoto Prefectural Yosanoumi Hospital, Kyoto, JapanAbstract: Mycoplasma species cannot be identified by routine bacteriological culture methods and are resistant to common antimicrobial agents. Mycoplasma hominis usually colonizes the lower urogenital tract and causes pyelonephritis, pelvic inflammatory disease, chorioamnionitis, rupture of fetal membranes, preterm labor, postpartum fever, postabortal fever, and neonatal infection. This organism is highly prevalent in cervicovaginal cultures of sexually active women. M. hominis, M. genitalis, Ureaplasma urealyticum, and U. parvum may invade and infect placental and fetal tissues, leading to adverse pregnancy outcomes. M. hominis occasionally causes nongenitourinary infection of the blood, wounds, central nervous system, joints, or respiratory tract. We present a case of a 27-year-old woman who developed abdominal wound hematoma and abscess after cesarean section. The wound was drained, but her high fever persisted, in spite of antibiotic treatment using flomoxef sodium and imipenem•cilastatin sodium. Because the exudate exhibited M. hominis growth in an anaerobic environment, we administered the quinolone ciprofloxacin. This therapy resolved her fever, and her white blood cell count and C-reactive protein level diminished to the normal ranges. To our knowledge, there are four published articles regarding the isolation of M. hominis from postcesarean incisions. Based on the current study and the literature, infection by this pathogen may cause hematoma formation with or without abscess after cesarean section or in immunosuppressed postoperative patients. In such cases, physicians may need to suspect Mycoplasma infection and initiate appropriate antibacterial treatment as soon as possible in order to avoid persistent fever.Keywords: Mycoplasma hominis, cesarean section, hematoma, abscess